PELAGIC FISHERY RESOURCES OF LAWSON'S BAY, WALTAIR - Rao, K Venkata Subba; Rao, V Ramamohana; Mojumder, P; Rao, T Appa; Reuben, S; Dan, S S; Rao, B Narayana (Indian Journal of Fisheries, 2011)
At Lawson's B;y, the gears employed are shoreseines, boatseines, hooksand lines, surface g!llnets and bottom-set nylon nets. During the period 1970 to1974, the estimated total annual landings by all gears were 654. 8, 62?.0', 577.